Temperature-Dependent Sheet Resistance and Surface Characterization of Thin Copper Films Bonded to FR4 Composite under Mechanical Vibrations - Sufyan Azam; Shadi Munshi; Mohamed K. Hassan; Alex Fragoso (Applied Sciences, 2023)
Electrical boards, also called printed circuit boards, constitute the basis of most electronic devices. These boards are mainly fabricated of thin copper films bonded to fiber epoxy laminates, such as FR4. Being the most important functional component of these devices, they sometimes undergo mechanical stresses such as shock and vibration during transport and operation that can induce electrical failure and malfunction; hence, studies addressing the effects of vibrations on their electrical properties have important applications. In this paper, small cantilever samples made of bare copper bonded to FR4 with three isolated rectangular zones were studied to analyze, for the first time, variations in electrical properties such as sheet resistance and resistivity before and after 200 k, 500 k, and 800 k vibration cycles at three different temperatures (25, 35, and 45 °C). A significant rise in resistance equivalent to 1657% of the initial value was observed from 0 to 800 k vibration cycles. These changes were accompanied by a 95% decrease in conductivity, from 4.1 × 107 to 2.3 × 106 S/m, whereas very little change in the electrical properties was observed due to temperature rise. Surface analysis by ESEM showed cracks ~1 µm in width and several millimeters in length with a crack density of ~8 cracks per mm after 800 k cycles. The surface composition (100% copper) was not altered even upon a high number of vibration cycles, and static drop contact angle measurements of 117–119 degrees indicated an increase in the hydrophobicity of the surface attributed to increased surface roughness and the accumulation of very small air bubbles on the cracks.